Perceived marketing intelligence and marketing communications tools used by rural Small, Medium and Micro Enterprise in South Africa - Lekhanya, Lawrence Mpele (Journal of Economics and Behavioral Studies, 2014)
Previous research revealed that Small, Medium and Micro Enterprises (SMMEs) have been struggling to grow including in rural and remote areas. However, there is little empirical research into how SMMEs promote themselves. To date is not clear about what marketing intelligence and marketing promotional communications they use. The survey intends looking to make contribution in closing research gap by seeking to understand the marketing intelligence and marketing promotional communications tools used by rural SMMEs and to what extent they used these tools and what are the limitations they have. This research aims to examine the perceived marketing intelligence and marketing communications tools used by South African rural SMMEs , to identify limiting factors to the used and establish the extend to use and their implications. The study population consisted of 374 respondents in five rural areas of KwaZulu – Natal province in South Africa (Empangeni, Ulundi, Nquthu, Escourt and Kwa-Nongoma). A quota sampling method was used to determine desired target population. Quantitative Likert scale questionnaire was designed and personal distributed to the respondents. Respondents were giving 7 days to complete questionnaire. Data analysis was done using SPSS (21.0) version. Figures and tables were used to present research findings. Statistical analysis revealed that marketing intelligence and marketing promotional tools were applied and found to be significant. The study found that promotional communication tools that cover both marketing promotional mix and marketing intelligence used by rural SMMEs are significant (p=.000*)